When women deliver at home with no one present: Are health care systems in Uganda driving women away? - Atukunda, Esther Cathyln; Mugyenyi, Godfrey Rwambuka; Obua, Celestino; Najjuma, Josephine; Aturinda, Isaac; Agaba, Edgar; Ware, Norma C.; Matthews, Lynn T. (Research square, 2019)
Background: Uganda’s maternal mortality remains unacceptably high, with thousands of women and newborns still dying of preventable deaths from pregnancy and childbirth-related complications. Despite the fact that over 95% of women in Uganda attend at least one antenatal care (ANC) visit, over 30% of women still deliver at home with no skilled birth attendant, many choosing to come to hospital after experiencing a complication. We explored barriers to women’s decisions to deliver in a health care facility among postpartum women in rural southwestern Uganda, to ultimately inform interventions aimed at improving skilled facility births. Methods: Between December 2018 and March 2019, we conducted in-depth qualitative face-to-face interviews with 30 post-partum women delivering at home or health facility in rural southwestern Uganda. The purposeful sample was intended to represent women with differing experiences of pregnancy, delivery and ANC. Women were recruited from 10 villages within 20km of a referral hospital. Interviews were conducted and digitally recorded in a private setting by a trained native speaker. Translated transcripts were generated and coded. Coded data was iteratively reviewed and sorted to derive descriptive categories using grounded theory methodology. Results: Regardless of where they decided to give birth, women wished to deliver in a supportive, respectful, responsive and loving environment. The data revealed six key barriers to women’s decisions to deliver from a health care facility: 1) Fear of unresponsive care, fueling a fear of being neglected or abandoned while at the facility, 2) fear of embarrassment and mistreatment by health care providers, 3)low perception of risk associated with pregnancy and childbirth, 4) preferences for particular birthing positions and their outcome expectations, 5) perceived lack of privacy in public facilities, and 6) perceived poor clinical and interpersonal skills of health providers to adequately explain birthing procedures or support expectant or laboring women and their newborn. Conclusion: Anticipation of unsupportive, unresponsive, disrespectful treatment, and a perceived lack of tolerance for simple, non-harmful traditions prevent women from delivering at health facilities. Building better interpersonal relationships between patients and providers within health systems could reinforce trust, confidence, improve patient-provider interaction, and facilitate useful information transfer during ANC and delivery visits.
Keywords: Health care systems; Uganda; Women